(untitled) (Research, Society and Development, 2020)
The objective is to identify the profile and social stigmas faced by pregnant women using crack abuse and to understand the main obstetric complications due to crack abuse. The methodology use the integrative literature review with a qualitative approach and a descriptive approach carried out in a LILACS and BDENF database, where the inclusion criteria were: articles in Portuguese, available for reading, full text, with a 7-year time frame (2014-2020). The exclusion criteria ruled out repeated article so articles that did not apply to the theme. After applying the criteria, 5 articles were selected to compose the study. Result: Difficulties were observed in attracting these women to health services. There is a certain blockage and unpreparedness of professionals to deal with and lead to the theme. Conclusions: It is concluded that studies that address the issue of crack consumption among women are rare and punctual Discussing about crack goes far beyond pointing out the effects or consequences of abusive consumption, as it is mainly the social impact that this consumption provides. It was observed that the prejudice and stigma of health professionals to wards women who abuse crack contributes to the maintenance of consumption “on the sly” It is important that health professionals from the whole network, and not only those from maternity, are prepared to deal with the issue, especially in the circumstances of pregnant women who abuse crack.